A CRITICAL ANALYSIS OF TRANSGENDER VISIBILITY AND RESPECTABILITY IN BHIMA JEWELLERY’S 'PURE AS LOVE' CAMPAIGN - Paul, R. Baiju; Benziker, Paul T. (International Journal of Research -GRANTHAALAYAH, 2025)
The present study explores the representation of transgender identity in Indian advertising, with particular reference to the Bhima Jewellery advertisement “Pure as Love” (2021). While representations of transgender individuals are gradually increasing in Indian media, there remains a significant gap in scholarly analysis, particularly within commercial advertising contexts. Drawing on Stuart Hall’s Media Representation Theory, this study explores how gender identity, cultural acceptance, and emotional narratives are constructed through visual imagery, sound design, and symbolic elements. A qualitative, frame-by-frame content analysis is employed to uncover the advertisement’s narrative strategies and ideological underpinnings, offering a deeper understanding of how mainstream media negotiates inclusivity within prevailing cultural norms. The findings show that although the advertisement presents a positive story about a trans woman being accepted by her family, it also supports traditional gender roles. The main character is shown through familiar signs of femininity like wearing bridal jewellery, showing emotional sensitivity, and seeking approval from her parents. This suggests that acceptance depends on fitting into cultural norms, reflecting Stuart Hall’s idea of dominant-hegemonic meaning. The advertisement also ignores important issues such as caste, class, and religion, creating a clean and idealized version of what it means to be transgender in India. This study adds to gender and media research by offering a critical view of how Indian advertisements handle the idea of inclusion within a consumer-driven system. It also gives useful suggestions for advertisers and media creators who want to represent marginalized communities in a more honest and respectful way.